Endogenous Norm Formation Over the Life Cycle – The Case of Tax Evasion - Nordblom, Katarina
This paper offers an explanation to why the general observation that elderly hold stronger moral attitudes than young ones may be an age rather than a cohort effect. We apply mechanisms from social psychology to explain how personal norms may evolve over the life cycle. We assume that people update their norms influenced by their own past behavior (e.g., cognitive dissonance) and/or by the attitudes of their peers (normative conformity). We apply the theory on actual norm distributions for young and old concerning tax evasion. Allowing for heterogeneous updating of norms where only those who identify with their network are actually conforming with it, while the others are only influenced by their own past behavior, we can explain the difference between young and old people’s moral values as an age effect through endogenous norm formation.Social norms; Endogenous norms; Tax evasion; Cognitive dissonance; Self-signaling; Normative conformity